Effectivité et ineffectivité des décisions de justice en matière matrimoniale : un exemple d'ineffectivité totale, le non-paiement de pensions alimentaires - Deleury, Édith (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The problem of non payment of maintenance orders has been widely recognized in many jurisdictions. It has attracted a considerable body of applied research and programm development. After reviewing, with statistical data, the ineffectiviness of Court enforcement procedures, the author analyzes the reasons for non enforcement and the remedies which have been adopted in the Province of Quebec. The author distinguishes between what she calls preventive remedies, collecting and penalties. Lastly, she concludes that the problem goes far beyond the law and that a re-thinking of the issues involved, particularly at the economic level, remains a necessity.